(untitled) (Journal Edutama Multidisciplinary Indonesian, 2024)
Perineal wounds can cause discomfort after delivery, which has a negative impact on the condition of the postpartum mother and baby if not treated quickly. Mothers often feel anxious when moving, which can inhibit the release of lochia and cause uterine subinvolution, increasing the risk of bleeding and infection. This discomfort can also interfere with the breastfeeding process, potentially resulting in failure of exclusive breastfeeding which has an impact on infant nutrition. This study aims to provide nursing care for postpartum discomfort due to perineal wounds at the Bendan Regional Public Hospital, Pekalongan City. The research method used is descriptive with a two-subject approach that meets the inclusion and exclusion criteria. The results showed that both patient nursing problems could be resolved through postpartum nursing interventions. After three days of treatment, both patients experienced a decrease in pain, with the pain scale decreasing to 1-3, from moderate pain to mild pain, and showed normal vital signs and felt more relaxed. Postpartum nursing actions and progressive muscle relaxation therapy have proven effective in overcoming postpartum discomfort due to perineal wounds in both respondents.